Share Of Deaths Classified as Cases with Insufficiently Defined Causes аs а Characteristic of the Quality of Mortality Data in Ukraine - Ryngach, N. О. (Statistika Ukraïni, 2022)
Reliable identification of the causes of each death and its correct classification ensures the quality of the mortality data. The large structural share of deaths with insufficiently clear causes reflects the existence of significant problems with determining the causes of death and their coding. The aim of the work is to assess the quality of data on mortality by cause in Ukraine through the prism of the contribution to official statistics of deaths classified as cases with insufficiently defined / ill-defined causes, and to characterize the scope and structural share of different causes, including sex and aggregate age groups. The calculations based on data from the State Statistics Service of Ukraine on the distribution of deaths by sex and age in 2019 and 2020. Elements of the WHO-recommended analysis tool (ANACoD), an electronic tool (Analytical Mortality Level and Cause-of-Death) (ANACoD), were used to estimate the proportion of deaths classified as cases with ill-defined causes. In 2020, Ukraine had a lower proportion of deaths in Class XVIII (3.2% versus 4.25% in 2019). At the same time, the level has not changed compared to 2019 (standardized according to European standards were 35.2 per 100 thousand people and 33.6 per 100 thousand people, respectively). For women, the causes of Class XVIII were more significant than for men (third position in the structure of mortality). The share of deaths classified according to the proposed list in 2020 in Ukraine reached 9% of the total number of deaths. For the population under the age of 65, the percentage of deaths with ill-defined causes (5.72%) exceeded the limit of 5%. In 2020, 35% of deaths with ill-defined causes fall into the specific Class XVIII, the rest - in the group of cases with vague or unspecific diagnoses. Generalized and unspecified atherosclerosis accounted for a quarter and intentional injuries – for a tenth of all deaths with ill-defined causes. Analysis of the mortality structure with an assessment of the contribution of deaths with insufficiently clear causes is necessary to understand the shortcomings in the quality of mortality data and their scale. It is also useful to develop measures to improve the processes of determining the cause of death and classifying the information obtained on mortality.